Keummian Nabi Muhammad dalam Periwayatan Hadis Qudsi - Elenia, Stevani (Al-Jadwa: Jurnal Studi Islam, 2023)
Hadith qudsi is one type of revelation conveyed by Allah and includes the type of khafi/dharuri revelation. In its transmission, the hadith qudsi was verbalized by the Prophet Muhammad, in contrast to the Qur'an, which must be conveyed according to what was received. Hadith qudsi is different from hadith in general because the hadith qudsi is based on Allah. This is because the messages contained in the hadith qudsi contain Allah's sciences which were previously unknown to humans, then conveyed to the Prophet as an explanation of the Qur'an as well as dharuriyat sciences. As Nabiyyi> al-ummiyyi (the deaf illiterate Prophet), the question will arise about the process of transmission from Gabriel to the Prophet Muhammad. Therefore an analysis was carried out using the Library Research method, to answer this problem. With this method, three ways can be found that the Prophet used in narrating hadith qudsi, namely through the intermediary of Jibril by memorizing all the messages conveyed by Gabriel, then understanding with all his intelligence (fatanah). In addition, Jibril also breathed knowledge into the heart of the Prophet, so in this case the Prophet narrated knowledge according to his own meaning which had been guaranteed by Allah to be true.